Association of subclinical atherosclerosis using carotid intima-media thickness, carotid plaque, and coronary calcium score with left ventricular dyssynchrony: The multi-ethnic Study of Atherosclerosis. Issue 2 (April 2015) - Sharma, Ravi K.; Donekal, Sirisha; Rosen, Boaz D.; Tattersall, Matthew C.; Volpe, Gustavo J.; Ambale-Venkatesh, Bharath; Nasir, Khurram; Wu, Colin O.; Polak, Joseph F.; Korcarz, Claudia E.; Stein, James H.; Carr, James; et al.
Abstract Background The role of atherosclerosis in the progression of global left ventricular dysfunction and cardiovascular events has been well recognized. Left ventricular (LV) dyssynchrony is a measure of regional myocardial dysfunction. Our objective was to investigate the relationship of subclinical atherosclerosis with mechanical LV dyssynchrony in a population-based asymptomatic multi-ethnic cohort. Methods and Results Participants of the Multi-Ethnic Study of Atherosclerosis (MESA) at exam 5 were evaluated using 1.5T cardiac magnetic resonance (CMR) imaging, carotid ultrasound (n = 2062) for common carotid artery (CCA) and internal carotid artery (ICA) intima-media thickness (IMT), and cardiac computed tomography (n = 2039) for coronary artery calcium (CAC) assessment (Agatston method). Dyssynchrony indices were defined as the standard deviation of time to peak systolic circumferential strain (SD-TPS) and the difference between maximum and minimum (max-min) time to peak strain using harmonic phase imaging in 12 segments (3-slices × 4 segments). Multivariable regression analyses were performed to assess associations after adjusting for participant demographics, cardiovascular risk factors, LV mass, and ejection fraction. In multivariable analyses, SD-TPS was significantly related to measures of atherosclerosis, including CCA-IMT (8.7 ms/mm change in IMT, p = 0.020), ICA-IMT (19.2 ms/mm change in IMT, p < 0.001), carotid plaque score (1.2 ms/unit change in score, p < 0.001), and log transformed CAC+1 (0.66 ms/unit log-CAC+1, p = 0.018). These findings were consistent with other parameter of LV dyssynchrony i.e. max–min. Conclusion In the MESA cohort, measures of atherosclerosis are associated with parameters of subclinical LV dyssynchrony in the absence of clinical coronary event and left-bundle-branch block.